2023
DOI: 10.1186/s13643-023-02264-8
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sports participation on mental health and social outcomes in adults: a systematic review and the ‘Mental Health through Sport’ conceptual model

Abstract: Background Sport is a subset of physical activity that can be particularly beneficial for short-and-long-term physical and mental health, and social outcomes in adults. This study presents the results of an updated systematic review of the mental health and social outcomes of community and elite-level sport participation for adults. The findings have informed the development of the ‘Mental Health through Sport’ conceptual model for adults. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 57 publications
1
19
0
1
Order By: Relevance
“…Consistent with the existing literature [ 19 , 83 ], the correlational analyses conducted in this study highlight that those athletes who reported higher levels of general health also showed higher levels of physical activity, enhanced coping capacities, elevated cognitive flexibility, and reduced cognitive fusion. In addition, cognitive flexibility may impact adherence and performance in physical activity, hence increasing the motivation for people of all age groups to participate in physical endeavors.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with the existing literature [ 19 , 83 ], the correlational analyses conducted in this study highlight that those athletes who reported higher levels of general health also showed higher levels of physical activity, enhanced coping capacities, elevated cognitive flexibility, and reduced cognitive fusion. In addition, cognitive flexibility may impact adherence and performance in physical activity, hence increasing the motivation for people of all age groups to participate in physical endeavors.…”
Section: Discussionsupporting
confidence: 89%
“…Engaging in regular physical activity yields numerous bodily benefits, such as the prevention of various health-threatening conditions (e.g., cardiovascular issues, high blood pressure, type 2 diabetes) [ 14 , 15 , 16 , 17 , 18 ]. Additionally, it significantly influences mood and mental well-being [ 19 , 20 , 21 , 22 , 23 ]. Furthermore, particularly in adolescents, engaging in physical exercise is crucial as it facilitates the enhancement of motor abilities, such as coordination, agility, explosiveness, dynamic and static balance, and the growth of muscular mass [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sport generally promotes a balanced relationship with the corporeal dimension, thus educating practitioners to perceive and use it both as a performative and expressive/relational tool ( 63 , 64 ). The results concerning body image, evaluated through the DKB-35 questionnaire, revealed no statistically significant differences between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Improving the health status of our population is a global priority, with PA being a core element of attaining and maintaining optimal health. Sports, a subset of physical activity, has shown to be particularly beneficial for facilitating a range of positive physical, mental, and social health outcomes [ 3 , 30 ]. Therefore, sports coaches are perfectly positioned to help participants develop movement patterns and motor skill competencies, which are important for lifelong PA participation.…”
Section: Discussionmentioning
confidence: 99%
“…Participation in individual and team sports has shown to be beneficial to physical, social, psychological, and cognitive health outcomes [ 1 , 2 , 3 ], and these benefits often provide additional or more potent health benefits than those achieved through other types of physical activities. The public health benefits of participating in sports are far-reaching, given that ~70% of children and adolescents and up to 40% of adults participate in some form of individual or team sport [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%